If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9x + 8y = 0 Solving -9x + 8y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8y' to each side of the equation. -9x + 8y + -8y = 0 + -8y Combine like terms: 8y + -8y = 0 -9x + 0 = 0 + -8y -9x = 0 + -8y Remove the zero: -9x = -8y Divide each side by '-9'. x = 0.8888888889y Simplifying x = 0.8888888889y
| 8[-0.5-(-2-5)]= | | 6(2x-3)=10(x+1)+6 | | 7x-7=50 | | -7x+5y+3y-2x= | | p^2p/p^-7 | | 14(v+4)-2v=3(4v+3)-18 | | -4x+8x-x+3x= | | 100.00-20%= | | 22/7•7 | | 450=.20*x | | 155=-0.1Q^2+10Q-90 | | 6(2x-3)=-40 | | 3x/3x-2-2/3x-2≠2/3 | | 8m-25=39mis | | 5+6t=10-7 | | 36x-96= | | 3x-4=5x-24 | | 1/3n-6=15 | | 30*365= | | 32x=16x^2 | | tan^2+4tan+2=0 | | 9-4n=7 | | 8m-25=30 | | 3x-4+10x-48=180 | | 3x-(x-(x-3))=-1 | | 3x-4+5x-12=180 | | (252)1/5 | | 8(t-4)+4t=4(3t+5)-10 | | 10(x-1)+4=12x | | 3*x-7=4*4+2 | | 8-2(t+5)=-2t-2 | | 3x/2-(x-1)/3=x/6 |